Design Of A Circularly Polarized Antenna At 2.45GHz With Harmonic Suppression For Material Characterization - Meor Said, Maizatul Alice; Misran, Mohamad Harris; Zakaria, Zahriladha; Mohd Zin, Muhamad Fakhrur Razy; Muhammad, Lailatul Niza (World Academy of Research in Science and Engineering, 2020)
Circular polarization is necessary in antenna applications especially for energy harvesting as matching the polarization in both the receiving and transmitting antennas can decrease the transmission losses. To achieve this matching, the transmitter and the receiver should have the same sense of polarization, axial ratio and the same spatial orientation. As the waves in our surroundings could be randomly propagating due to human body or device movements in wireless technologies applications such as RFID, GPS and WLAN, circular polarization comes in handy to reduce the effect of multipath reflections, enhances weather penetration and allows for the mobility of both the transmitter and the receiver. The objective of this paper is to design a circularly polarized microstrip antenna that operates at 2.45 GHz with harmonic suppression for energy harvesting applications. Single feeding technique is used because of its simplicity, cost efficient, easy to fabricate, and compact size. This paper presents a new design of a circularly polarized antenna with harmonic suppression based on a rectangular microstrip patch. Two truncated edges placed on the opposite side of the patch antenna generate circular polarization. The truncation technique is used to be able to split the field into two orthogonal modes with 90° phase shift of equal magnitude